Shepherding: An Immune-Inspired Robotics Approach - Razali, Sazalinsyah; Meng, Qinggang; Yang, Shuang-Hua (2010)
In this research, basic biological immune systems and their responses to external elements to maintain an organism’s health state are used as an inspiration for solving a specific multi-robot system problem. The proposed algorithm is based on immune network theories that have many similarities with the multi-robot systems domain. The approach uses a memory-based immune network that enhances a robot’s action-selection process and can obtain an overall a quick group response. The algorithm is applied on the Player/Stage simulation platform and evaluated using the sheepdog scenario. The project proceeds to investigate the low-level shepherding behaviour, specifically the shepherds' Line Formation.